Explaining differences in the returns to R&D in Argentina: the role of contextual factors - Arza, Valeria (2022)
Argentinean firms’ investments in R&D are well below its regional peers. One potential explanation for this fact is the existence of low and heterogeneous returns for these investments. This paper uses novel microdata to estimate the returns to R&D and analyse the role of contextual factors in shaping its heterogeneity. The findings confirm that returns are indeed heterogeneous and depend on some important factors related to the market context, such as measures of uncertainty; and the knowledge context, such as knowledge spillovers. Acknowledging that heterogeneity of returns depends on firms’ context is crucial for designing innovation policies to boost private R&D returns.